IN VITRO REGENERATION STUDIES IN STEVIA THROUGH NODAL SEGMENT AND SHOOT TIP - S. V. PAWAR; V. G. KHANDAGALE; V. M. JAMBHALE; A. S. JADHAV; B. D. PAWAR (The Bioscan, 2015)
In vitro regeneration protocol was standardized for propagation of promising newly introduced non caloric sweetener and an antidiabetic medicinal plant Stevia rebaudiana. Nodal segment and shoot tip was used as an explants. Surface sterilization with HgCl2 for 3 minutes gave best result of disinfection with maximum survival of explants for nodal segment and shoot tip also. For initiation MS + 1 mg L-1 BAP media was found best performing media. Maximum number of shoots per plant were observed on media MS + 2 mg L-1 BAP for both nodal segment and shoot tip explants.MS + 2 mg L-1 BAP media was found most promising media. Highest in vitro rooting (62.3 %) was obtained within 12.3 days on MSB5 media supplemented with1mg/l NAA. During hardening of rooted plants, 70% plantlet survival was observed on cocopeat in green house.